Non-use and inadequate use of cervical cancer screening among a representative sample of women in the United States - Narcisse, Marie-Rachelle; McElfish, Pearl A.; Hallgren, Emily; Pierre-Joseph, Natalie; Felix, Holly C. (Frontiers in Public Health, 2024)
Introduction. Women’s adherence to the United States (U.S.) Preventive Services Task Force guidelines for cervical cancer screening was determined by examining predisposing, enabling, and needs factors from Andersen's Behavioral Model of Health Services Use conceptual framework. Methods. The outcome was operationalized as cervical cancer screening Use, Non-Use, and Inadequate-Use. Multinomial logistic regression was conducted on data from the 2019 National Health Interview Survey of 7,331 eligible women aged 21-65. Results. Compared with women who used cervical cancer screening services, women aged 30-65 were less likely to be Non-Users than those aged 21-29. Hispanic, Asian, and American Indian/Alaska Native (AIAN) women were more likely to be Non-Users than White women. More educated women were less likely to be Non-Users. Foreign-born women <10 years in the U.S. were more likely to be Non-Users than U.S.-born women. Women with financial hardship were less likely to be Non-Users. Poorer women and uninsured women were more likely to be Non-Users. Women with children in their household were less likely to be Non-Users than those without children. Women who had a well-visit in the past year were less likely to be Non-Users. Women with a history of HPV vaccination were less likely to be Non-Users. Compared with women who used cervical cancer screening services, women aged 30-65 were less likely to be Inadequate-Users. AIAN women were more likely to be Inadequate-Users. Women of other races were less likely to be Inadequate-Users. Employed women were less likely to be Inadequate-Users. Uninsured women were more likely to be Inadequate-Users. Women who had a well-visit within a year were less likely to be Inadequate-Users. Women with past HPV vaccination were more likely to be Inadequate-Users. Smokers were less likely to be Inadequate-Users. Discussion. Predisposing, enabling, and needs factors are differently associated with non-use and inadequate use of cervical cancer screening. Understanding factors associated with the use, non-use, and inadequate use of cervical cancer screening is crucial to avoid or curb unnecessary tests, increased costs to both society and individuals, and the ill-allocation of limited resources.